Causes of medication errors in community pharmacies: A meta-ethnography and systematic review - Maguy Saffouh El Hajj; Anna Robinson-Barella; Andy Husband; Adam Todd (PLoS ONE, 2026)
Introduction Medication errors are a leading cause of patient harm and account for thousands of deaths and injuries annually. While medication safety efforts have primarily targeted hospital settings, community pharmacies are also prone to such errors due to their high patient access and utilisation. This review utilised a meta-ethnographic qualitative approach to synthesise findings from available primary qualitative research about the causes of medication safety issues and errors in community pharmacies as well as the contributing factors. Materials and methods This meta-ethnographic systematic review was conducted in line with Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) and the meta-ethnography reporting guidance (eMERGe) and framework and registered on PROSPERO. Eligible studies were identified using a comprehensive search strategy across multiple databases and grey literature sources, without language or date restrictions. Qualitative data were synthesised using Noblit and Hare’s seven-phase meta-ethnographic approach, generating third-order constructs that captured underlying causes of medication errors in community pharmacies. Confidence in the findings was assessed using the GRADE-CERQual framework. Results Thirteen studies were included in the review with the majority from the United States and England. Most studies (n = 10) used qualitative research designs while two studies utilised a mixed-methods approach. Through meta-ethnographic synthesis, five third-order constructs (themes) were developed to represent the factors contributing to medication errors in community pharmacies. These themes included: 1) pharmacist-related factors, 2) the environment within the pharmacy 3) management and financial related factors 4) organisational and social environment within the pharmacy and 5) challenges with digital technologies. Conclusions This meta-ethnographic systematic review identified five themes contributing to medication errors in community pharmacies. The review findings offer valuable insight for guiding the design of future tailored safety initiatives. Understanding the complex interplay between these contributing factors is essential for enhancing medication safety and informing future research and practice in real-life community pharmacy settings.